Business performance evaluation of tuna handlines operated in fish aggregating device areas: a case study in Bone Regency, South Sulawesi Province, Indonesia - Pontoh, Peggy; Rumpa , Arham; Asia; Kun, Anang Rahmat; Krisnafi , Yaser; Syamsuddin , Muhidin; Rasdam; Kasim , Muh.; Runtukahu, Muhammad Ikhsan Zulfatan; Baroqi, A. Riza; Timur, Putra Satria (Universitas Sam Ratulangi, 2024)
The difference in fishermen's catches each year tends to fluctuate at different fishing locations; this is due to the still low efficiency and productivity of fishing efforts. The purpose of the study was to evaluate the performance of tuna handline businesses operated in fish aggregating device areas at fishing grounds in FMAs 713 and 714. The results show that in the period of 2020-2023, the development of catch rates each year fluctuated, while the average value of catch rates for each vessel based on the highest season occurred in the East Season and the lowest in the Transition Season I. Likewise, the average catch rate based on the time of the month of capture is highest in June, July, and November. The results of the analysis of production factors that influence the catch are the time of the month of fishing, fuel use, ice use, and number of crew members, while the factors of trip length, ship GT, and engine capacity do not have a direct influence. The information from this evaluation is very much needed by fishermen and stakeholders to optimise the performance of tuna handlines in fish-aggregating device areas.